ASSESSMEN• T OF IMPORTANT SEISMIC PROVISIONS OF EBCS 8 - 1995 FROM STRUCTURAL DYNAMICS PERSPECTIVE - Worku, Asrat (Zede Journal of Ethiopian Engineers and Architects, 2023)
In this paper, a/'J.attempt is made to assess some of the·important seismic provisions and speciflcation,s of the 1995 Ethiopian Building Code Standard (EBCS 8) from, the perspective of the theory of structural dynamics and principles of earthquake engineering. For this purpose, a concise but thorough theoretical background isprovided on the vibratiQn oj structural systems. Only horizontal .earthquake excitation of the systems is treated, as this causes the most important effects on building structures. lvfany.concepts that are unknown to the werage structural designer, but specified by the Code ,for strict adherence, are clarified and critically assessed.' The design spectra of the Code are compared with early research results that serv~d as the basis jor the prepal'ation of design spectra of many international codes. Existing discrepancies are shown and illustrated using an example problem. Important conclusions are drawn and some recommendations made. Comparison of the provisions of the Code with those of other international codes is not the intention of the paper. This is postponed to afuture work.